Anthropometric profile and limb asymmetries in young male and female fencers - Tsolakis, C.a b , Bogdanis, G.C.a , Vagenas, G.a (Journal of Human Movement Studies, 2006)
The aim of this study was to establish an anthropometric profile of young fencers separated into four different age groups and to examine the degree of upper and lower limb asymmetry. Selected anthropometric characteristics were measured in 152 fencers (84 males and 68 females) during the Greek fencing championships. Fencers were divided into 4 age categories (boys/girls, cadets, junior and senior) according to the International Fencing Federation rules. The larger differences in anthropometric characteristics of both males and females were observed between the very young group (10-13yrs) and the older groups, while for most parameters, there were no differences between the two older groups (18-20yrs and >20yrs). There was no significant difference between the 10-13yrs groups of males and females in almost all anthropometric characteristics. Somatotype ratings were relatively stable across age groups. The mean somatotype of male fencers was 3.1-2.6-3.2. The female fencers were mainly situated in the ectomorph -endomorph region, and had a mean somatotype of 3.8-1.8-3.3. Arm CSA was higher in males compared to females in all age groups, except for the 10-13yrs group. However, leg CSA was not different between genders in all age groups. Significant CSA asymmetries were observed between the dominant and the non-dominant sides in the arm and leg in both genders. Arm asymmetries were evident from an early age, while leg asymmetries were not observed in the younger group. The lack of significant differences between males and females for the 10-13yrs groups in most of the anthropometric characteristics, should be taken into account in talent selection. ©2006 Teviot Scientific Publications.